Critical factors of influence in the negotiation process; an empirical conceptualization. - C., José Barragán; P., Gerardo Cervantes (Revista Daena: International Journal of Good Conscience, 2019)
This documentation research explains the conceptualization of four critical factors that may have influence in the negotiation process, and how these factors could make negotiators feel as close or far to the position of power in a negotiation process. In which the role of negotiator can influence at the time, in getting the agreement as a final objective between parts involved, also, start analyzing how these approaches can turn the table in positions in negotiations.